2020
DOI: 10.1080/1034912x.2020.1843143
|View full text |Cite
|
Sign up to set email alerts
|

Learning, Social, and Psychological Outcomes of Students with Moderate, Severe, and Complex Disabilities in Inclusive Education: A Systematic Review

Abstract: The purpose of this systematic review was to investigate the learning, social, and psychological outcomes of students with moderate, severe, and complex disabilities (MSCD) in inclusive settings. The review discusses barriers to conducting rigorous research in this field. Whilst an initial literature search located 1,338 records, only 18 were finally included due to the eligibility criteria. Studies were placed in categories based on the topics investigated. Regarding learning outcomes of students with MSCD, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
(55 reference statements)
1
18
0
1
Order By: Relevance
“…There is recent research showing support for broadly inclusive policies (O’Rourke, 2015), but typically these are not based on consistent conceptual frames. Meta-analyses of research on inclusive education do exist (Göransson and Nilholm, 2014), with some studies focusing specifically on inclusive education (Dell’Anna et al, 2020; Van Mieghem et al, 2020), and also with multilingual methodologies (Amor et al, 2018). Nonetheless, they are somewhat disparate and few are focused on how researchers have investigated the phenomenon of inclusive education.…”
Section: Introductionmentioning
confidence: 99%
“…There is recent research showing support for broadly inclusive policies (O’Rourke, 2015), but typically these are not based on consistent conceptual frames. Meta-analyses of research on inclusive education do exist (Göransson and Nilholm, 2014), with some studies focusing specifically on inclusive education (Dell’Anna et al, 2020; Van Mieghem et al, 2020), and also with multilingual methodologies (Amor et al, 2018). Nonetheless, they are somewhat disparate and few are focused on how researchers have investigated the phenomenon of inclusive education.…”
Section: Introductionmentioning
confidence: 99%
“…Here, “functioning” is defined as the overall well-being of a child in terms of physical health (body structures and body functions), activities (e.g., activities of daily life), and social health (e.g., participation in various social events) [ 2 ]. The rehabilitation interventions can be provided at a health facility level or at the community level to improve the functioning and health of children with severe malaria-related disability, education, inclusion, and social participation [ 42 , 43 ]. Such a service also includes early identification and providing rehabilitation support for children with severe malaria-related disability by establishing screening mechanisms (prevention of further disability).…”
Section: Methodsmentioning
confidence: 99%
“…Since the establishment of the Salamanca Statement in 1994, most countries around the world have enacted laws and legislations to maintain IE systems and have seen a tremendous increase in research in this area, especially in Western countries [4,5]. Over the last decade, a large body of research has suggested that IE is the best practice for students with disabilities, as it increases their academic performance and achievement, creates opportunities to seek higher education, improves vocational skills, develops developmental skills, and reduces maladaptive behaviors [2,[5][6][7][8][9][10][11].…”
Section: Introduction 1inclusive Educationmentioning
confidence: 99%